(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Grid electricity supply in Nigeria is inadequate and epileptic. Households and businesses use generators for electricity provision with wide-ranging negative impacts on the economy and environment. Wind as a renewable energy is an option to the use of generators in electricity generation. This study aims to compare the performance of an improved design wind turbine against a conventional wind turbine and a diesel generator for off-grid electricity generation in Kano, Nigeria. The annual energy production, levelized cost of electricity (LCOE) and net present value (NPV) were used for making comparison over a 20-year common life span for Polaris P10-20 turbine, PLEB turbine and a 20kW rated diesel generator. Diesel generator produced highest annual energy output of 61,320kWh against 22,145kWh and 24,159kWh for Polaris and PLEB turbines respectively. The diesel generator had least LCOE of 0.14/kWh against 0.37/kWh and 0.27/kWh for Polaris and PLEB turbines respectively. The NPV of diesel generator is 91,611 negative with no internal rate of return (IRR). It had 90,000 negative cashflow and no payback. The Polaris turbine had negative NPV of 21,386, IRR of 5.03% and could not payback its investment. PLEB turbine had positive NPV of 10,838, IRR of 12.08% and payback period of 12 years. The study has shown that with right investment and environmental policies, deployment of wind turbines for electricity generation in Kano is viable.